Supervisors’ Challenges with Online Supervision Using Microsoft Teams in Supervising Open Distance and E-Learning (ODeL) Pre-Service Teachers (Teacher Education through Flexible Learning in Africa (TETFLE), 2024)
Online supervision has been introduced to the field of education. However, prior to the COVID-19 pandemic, university pre-service programmes did not provide pre-service teachers and supervisors with online teaching practice experience. Microsoft Teams (MS Teams) has proven to be an indispensable tool in facilitating online supervision. The Domestication Theory was used as a lens to explore the challenges supervisors faced with online supervision, using MS Teams in an Open Distance and e-Learning (ODeL) institution in South Africa. This study adopted an exploratory case study design, using semi-structured interviews. Eight supervisors were purposefully selected to participate in the study. Thematic analysis was employed to analyse the data. The findings of this study showed that poor communication between supervisors and pre-service teachers, the lack of digital literacy among pre-service teachers, the difficulty of network coverage, and providing feedback were some of the challenges that supervisors experienced during online supervision. This study recommends that training be conducted for supervisors and pre-service teachers in using MS Teams and its various functions before supervision. Further research should explore pre-service teachers’ engagement with online supervision tools to inform the future practice of teacher education programmes.
Keywords: Online Supervision; pre-service teachers; supervisors’ challenges; teaching practice; Microsoft Teams; ODeL